Development of solar-powered biodiesel reactor for Kuwait sheep tallow - Alajmi, Fnyees S. M. D. A. (2019)
Biodiesel is one of the recent green fuel production in the world, where it can be produced from several raw materials such as straight vegetable oils, animal fats, tallow and waste cooking oils etc, and blended with diesel. Properties of biodiesel are different compared to the fossil diesel in terms of production methods and emission levels released after the combustion in internal combustion engine. Kuwait consumes a huge amount of energy which is almost 8% to meet the increasing demand for electricity and water. Also, the use of electricity in the production of biodiesel adversely increases energy use and cost of production. While Kuwait is receiving the amount of irradiation from 2050 KWh/m² to 2100 KWh/m². Besides that, to the best of our knowledge there are no previous studies applied solar powered in producing biodiesel in Kuwait. The present study is concerned with the evaluation of the potential of using solar energy to produce biodiesel from sheep fat waste as a raw material due to its less cost, more efficient and renewable method. An experimental test rig was set up for a single cylinder diesel engine in the laboratory, where the solar system was used to assist the production process of biodiesel from tallow waste. The biodiesel is then blended with diesel at different volume percentages, such as graded as B20, B50, B75 and B100 respectively. The performance of the biodiesel was also investigated on a single-cylinder four-stroke diesel engine. The exhaust gases such as oxygen, carbon monoxide, carbon dioxide, nitric oxide and nitric dioxide where also analyzed. A solar system was designed and applied effectively to power the reactor for biodiesel production system. The designed solar system was consisted of solar cells, solar panels, two sources of electricity (12-volt DC and 240-volt AC power supply), adapter and 8-batteries. An optimum decrease values of nitric oxide level was observed at the load of 51%, 68%, 85% and 93% during the operation at blend of biodiesel B20, B50, B75, B100, respectively. Nitric dioxide was decreased at the load of 51%, 68% and 85% during the operation using of B20, B50, and B75. Optimum sfc was achieved at B20, B50, B75 during high loads of 85% and 93%. It can be concluded that sheep tallow biodiesel shows a promising result in terms of fuel consumption and environmental emissions of greenhouse gases.